THE IMPACTS OF PHILANTHROPY RESPONSIBILITY AND ETHICAL RESPONSIBILITY TOWARD CUSTOMER PURCHASE BEHAVIOR AND CUSTOMER LOYALTY - Kurniawati Chrisjatmiko; Danthy Margareth (Jurnal Manajemen dan Pemasaran Jasa, 2017)
The purpose of this research is to analyze the impact of philanthropy responsibility and ethical responsibility towards customer purchase behavior and customer loyalty on fast food restaurants. The research was conducted by using quantitative research design and hypothetical testing to explore philanthropic responsibility, ethical responsibility, customer purchase behavior, and customer loyalty variables. Samples were taken from 186 respondents of employee population in Jakarta. Structural equation modeling was used in order to test the proposed hypotheses. Research result showed the positive and significant impact of philanthropic responsibility towards customer purchase behavior. On contrary, there was no positive ethical responsibility impact found towards customer purchase behavior. These findings are supported by the fact that the majority of consumers purchased fast food base on impulsive buying and not driven by the fast food restaurants ethically responsible behavior. However, the research does show a positive and significant impact of customer purchase behavior on customer loyalty. Further research recommendation should be taken from more respondents in a broader population area. Companies are suggested to approach a strategic and relevant caused-related marketing and caused promotions in relation to philanthropy responsibility to increase customer purchase behavior.